DETERMINE THE RELATIONSHIPS OF FACTORS FORMATION OF YOUNG PEOPLE OVERWEIGHT - Shevchenko, Yu.; Golovanova, I.; Vesnina, L.; Kaidashev, I. (World of Medicine and Biology, 2015)
A definition of the relationships factors of increased body weight in people 18-25 years old. Examined 27 people of both sexes with overweight (BMI above 25 kg/m2) and 41 people with normal weight (BMI 18,5-24,9 kg/m2) in the control group. Based on the data obtained using correlation analysis and calculation of the odds ratio defined formation plausible relationships between factors underlying weight gain in patients of the main group - a violation by restrictive eating behavior and cognitive restrictive types, change in quality of life, excess intake of energy, increased basal metabolism, insulin resistance, changes in markers of chronic systemic inflammation and neuropeptides Agouti-related protein (AgRP) and Cocaine- and amphetamine- regulated transcript (CART). Suggested that the interaction signaling mechanisms hypothalamic regulation of energy homeostasis and signaling pathway nuclear transcription factor κB leads to the leveling system state preconditioning IκB/NF-κB and its stabilization and major components that mediate the monitoring of the activity of the main components of the signaling cascade proinflammatory way of NF-κB under conditions of normal and increased energy intake may serve orexigenic AgRP neuropeptide and anorexigenic - CART.
Keywords: neuropeptides; energy metabolism; nuclear transcription factor κB; overweight